IMPLEMENTASI METODE RESPONSE SURFACE SEBAGAI UPAYA OPTIMALISASI JUMLAH BINTIL AKAR PADA TANAMAN KEDELAI - Muchammad Aziz Chusen; Rukun Santoso; Rita Rahmawati (Jurnal Gaussian, 2017)
Response surface method is a set of statistics and mathematical techniques, useful to analyze the issue of multiple independent variables that affect to the dependent variable of response, and aim to optimize the response. The existence of response surface method is able to assist researchers in conducting improvised to get optimum results accurately and efficiently. In this experiment using the data factorial CRD (completely randomized design) with two factors and three levels. Two factors were tested consists of the elements cobalt and ferrum, with the level in the form of element concentrations with each ie cobalt (0 mg/L, 0.1 mg/L and 0.2 mg/L), and ferrum (0 mg/L, 1mg/L and 2 mg / L). Variable response is the number of nodules roots of soybean crops. After testing the response surface method produced a linear model of the first order Jumlah Bintil Akar Kedelai = 10.3 + 10.2 Ferum + 238.3 Kobalt – 1340.1 Kobalt 2  –  93 Ferum*(Kobalt 2). with the value of concentration at ferum = 2 mg/L and cobalt = 0.1 mg/L is able to generate growth in the number of nodules optimum soybean crop in these experiments. Keywords: Factorial design, Response surface